MILLENIAL MENTAL HEALTH EXPLORATION - Dwina Rizki Febrianti; Yayan Firmansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study was conducted to determine how much influence work stress has on employee performance seen through mental health on millennial generation employees born 1981 to 1996 in Bandung City. The method used in this research is casual quantitative method. The primary data of this study used a questionnaire survey, and secondary data were obtained through articles, journal publications and theory books. Data collection in this study used a questionnaire distributed to millennial generation employees in Bandung City online and offline. The technique used in sampling used non-probility sampling with purposive sampling technique. Sampling taken was 398 respondents. Respondents were taken based on age, gender and employment criteria. The data analysis method in this study uses smartPLS software. Data testing through validity, reliability and hypothesis testing. Based on the results of the study, it shows that the work stress variable (X) has a significant effect on the employee performance variable of 0.096. Work stress variables and mental health have a significant effect on employee performance variables on millennial generation employees born 1981 to 1996 in Bandung City, namely 0.012